LIBRARY AND INFORMATION SCIENCE (LIS) EDUCATION AND PROFESSIONAL DEVELOPMENT: A CASE STUDY - Jagmohan Meena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This case study investigates the landscape of Library and Information Science (LIS) education and professional development, focusing on the evolving needs and expectations of library professionals in a digital age. The study examines various educational programs, curricula, and continuing professional development (CPD) opportunities available to LIS professionals. It also addresses the challenges faced by educational institutions in adapting to the rapid technological advancements impacting the information sector. By analyzing data collected from surveys, interviews, and literature reviews, this research aims to highlight effective strategies for enhancing LIS education and professional development. The findings underscore the necessity for LIS programs to embrace innovation, foster collaboration, and prioritize critical information literacy skills to prepare future librarians for the challenges of the 21st century.